TROPHIC INTERACTIONS OF THE FISH COMMUNITIES IN CIRATA RESERVOIR, WEST JAVA - Agus Arifin Sentosa; Astri Suryandari; Amula Nurfiarini (Research Center for Fisheries, 2021)
The utilization of food resources by the fish communities in the Cirata Reservoir depends on the environmental conditions of the reservoir. Eutrophication and the presence of potentially invasive alien fishes could affect the trophic interactions of food utilization by the fish communities in the Cirata reservoir. This study aimed to analyze the trophic interactions of the fish communities in the Cirata Reservoir, West Java. The samplings were conducted in October, December 2018, and April 2019. The fish samples were collected using experimental gill nets with different mesh sizes. The stomach contents were dissected to study their food habits under a stereoscopic microscope. Data analysis was performed using the index of preponderance, niche breadth, trophic level, and index Schoener. A total of 21 species of fishes in the Cirata Reservoir utilized food resources, including phytoplankton, zooplankton, aquatic plants/macrophytes, molluscs, insects (adult and larvae), worms, a body part of fishes and crustaceans, pellets and detritus. The fish communities had a wide range of niche between 0.00-0.32 and trophic levels between 2.00-3.63. The non-native fishes in the Cirata Reservoir had the food overlapping potential with native fishes, from low to high categories, especially from the Cichlidae. Trophic interaction of fish communities in the Cirata reservoir was still relatively stable, characterized by overlapping food niche in the low to medium categories. The fish stock enhancement effort such as fish introduction or restocking in the Cirata Reservoir could still be carried out with a precautionary approach to filling empty niches and avoiding the potential for invasive alien fish species.